PENERAPAN UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY MODEL UNTUK MENGUKUR PERILAKU PENGGUNA APLIKASI AKUNTANSI PADA USAHA KECIL DAN MENENGAH - Widanengsih, Euis (AGUSPATI Research Institute, 2021)
Information and telecommunications technology (ICT) is a driving factor for the movement of human lifestyles to a more modern and practical direction. Implementation of accounting applications that facilitate business processes should be utilized properly by Micro, Small and Medium Enterprises (MSMEs) in DKI Jakarta, because DKI Jakarta Jakarta is an economic center that has various supporting facilities that make it easier for MSMEs to develop. However, acceptance of the application of this technology depends on the business actors themselves. The purpose of this study is to measure the behavior of users of accounting applications using the UTAUT model. The data used in this study is primary data. Primary data is data obtained directly in the field. The data collection technique in this research is a survey. The sampling method uses a purposive sampling method with criteria for MSME owners who are located in DKI Jakarta and who have been running their business for at least two years and are still operating or currently operating, as well as knowing about accounting applications that can be used by MSMEs, including Zahir, Myob, Jurnal.id, Accurate, Buku Warung and Buku Kas. The survey was conducted during March - April 2021. The sample used in this study was 50 respondents. The data that has been collected is processed using the SEM method with the Partial Least Square (PLS) approach with the SmartPLS 3.0 software tool. The results of this study indicate that Performance Expectancy (PE) does not significantly affect Behavioral Intentions (BI). Effort Expectance (EE) or business expectations on the use of accounting applications does not significantly affect Behavioral Intentions (BI). Social Influence (SI) or social influence does not significantly affect Behavioral Intentions Behavioral Intentions (BI). Facilitating Conditions (FC) have a positive and significant effect on Use Behavior (UB) or user behavior. Behavioral Intentions (BI) has a positive and significant effect on Use Behavioral (UB)